Effects of Handgrip Relaxation on Decreasing Blood Pressure in Patients with Hypertension - Moomina Siauta; Selpina Embuai; Hani Tuasikal (Universitas Airlangga, 2019)
Hypertension is a leading cause of death if it is not properly treated. Handgrip relaxation is an intervention that can be used to reduce the blood pressure in patients with hypertension. The purpose of this study was to determine the effects of handgrip relaxation on decreasing blood pressure in patients with hypertension. This study used a pre-test-post-test design with a control group and it was conducted at RSUD Dr. M. Haulussy, Ambon. The sample consisted of 14 patients aged 18 to 75 who suffered from hypertension type 1 and 2. The sampling method was consecutive sampling and the patients were divided into the intervention (n=7) and control group (n=7). Handgrip relaxation was administered to the patients in the intervention group. The data was analyzed using a One-Way ANOVA test. The results showed a decrease in the systolic and diastolic blood pressures on the 3rd day with the highest mean value found in the intervention group and the control group had a significance value of 0.003 (p<0.05) and 0.014 (p<0.05) Handgrip relaxation had an effect on the decrease of systolic and diastolic blood pressures in patients with hypertension. Handgrip relaxation that was given for fifteen minutes over three days can be recommended as a nursing intervention to decrease the blood pressure of hypertensive patients.